The Effect Of Usıng Short Story Toward Students’ Achıevement In Vocabulary Mastery - Nur Azmi Rohimajaya; Deuis Zatnika (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2018)
The objective of this study was to obtain the empirical evidence about the effect of using short story toward students’ achievement in vocabulary mastery at the eighth grade students of SMPN 1 Labuan. The sample of this study was 70 students taken from the eighth grade of SMPN 1 Labuan. 35 students were from the experimental class and 35 students were from controlled class. The method used in this study was a quantitative method that designed the experimental. In collecting the data, the researcher conducted test twice to both the class in which one was as pre-test and another was post-test. And in analyzing the data, the researcher used t-test formula to find out whether there was a significant difference between two variables in this study. The result of statistic calculation obtained that the value of t-observation (to) was 22.191 and the degree of freedom (df) was 68. In the table of the significance 5%, the value of (df) = 68 was 1.667. By comparing the value of to (22.191) with the value of tt (1.667), it could be seen that the value of to was higher than the value of tt. Then, the alternative hypotheses (Ha) was accepted and the null hypotheses (Ho) was rejected. Based on the result, it could be concluded that the use of short story was more effective in teaching and learning reading comprehension toward students’ achievement in vocabulary mastery than without using short story